P245 "… No cleaning, no stairs, no sex…everything just stops": Understanding living with severe asthma to inform effective self-management. (12th November 2015) - Apps, LD; Hewitt, S; Green, R; Bradding, P; Murphy, A; Martin, N; Singh, SJ; Singh, SJ; Hudson, N; Evans, R
Abstract : Introduction and objectives: Despite the large socioeconomic burden of severe asthma, few studies have focused specifically on the patient experience of living with and managing severe asthma. Patient-related factors including behavioural, psychological and social factors complicate the management of the condition. This study aimed to explore these experiences in individuals with severe asthma to understand how to support effective self-management. Method: Semi-structured interviews were conducted with participants recruited from a difficult asthma service at Step 4–5 of the BTS/SIGN guidelines. Recruitment occurred until theoretical saturation was achieved. Interviews were transcribed verbatim and coded, supported by NVivo software (Version 10). Thematic analysis was performed. 1 Results: 29 interviews were completed (44% male, mean age 49.45 (13.64) years, BMI 31.65 (5.48) kg/m 2, 4 smokers). Five themes describe the experience of living with and managing severe asthma: Impact of asthma. Debilitating breathlessness was described impacting on many areas of participants lives, including relationships, work and family life. Day to day management of asthma. Self-regulatory behaviours were described such as monitoring peak flow and pacing. However, these behaviours and the implied restrictions could induce distress and dissatisfaction. This limited self-management behaviours in-between the acute phases of illness. Confidence to manage symptoms. Participants reported confidence to manage acute events, but the unpredictability of symptoms and fear of inducing symptoms appeared to undermine their confidence to manage symptoms. Challenges to effective self-management. There were further multiple challenges to effective self-management, such as: understanding of disease; perceptions of asthma by others; reluctance to accept hospitalisation and the unpredictability of symptoms. Beliefs about medication. There was conflict around long term oral steroids. Most participants resolved this by balancing the necessity of the medication versus the concerns they held about the long term effects of maintenance. There was little comment regarding inhaled medications. Conclusion: Strategies are needed to enhance acceptance and confidence to engage in self-management behaviours. This should encompass all aspects of the disease, not solely the acute phases, to minimise daily distress and increase effective self-management to improve the health status for this severe population. Reference: 1 Braun V. Using thematic analysis in psychology. Qualitative Research in Psychology . 2006;3 :77–101